Rancangan Program Pengembangan Kecerdasan Emosi dalam Aspek Empati Berbasis Teknologi Informasi - Dhea Ratu; Helma Helma; Fuaddillah Putra (Jurnal Counseling Care, 2021)
ABSTRACT This research is motivated by the presence of students who lack a sense of empathy, and there is no service program developed specifically to increase students' empathy. So that researchers are interested in designing service programs that can make it easier for BK teachers to develop student empathy. This study aims to determine: 1) Profile of the level of empathy of students; 2) designing development programs to improve adolescent emotional intelligence in the aspect of empathy based on Information Technology that can be accepted theoretically and practically. This research method is quantitative descriptive and developmental type. The data collection technique used is a questionnaire. The subjects in this study were students of class XII IPA 3, State High School 2 Bungo, totaling 33 people. Theoretical experts consist of 3 lecturers, practical experts are counselors and media experts are Information Technology teachers. The development procedure used in this research includes 5 steps, namely: 1) Potential and problems; 2) data collection; 3) product design, 4) design validation, 5) design revision. The data analysis technique used is the percentage. The results of the calculation of the score for each validation carried out are searched for the average score of the acquisition and then it can be converted from quantitative data to qualitative data. The results of this study revealed that: 1) the profile of the level of empathy of students was in the medium category; 2) applications that have been validated by theoretical, practical, and media experts are categorized as highly accepted. That is, the program developed is feasible to be used to increase the empathy of students at school. Keywords: Development programs, empathy, information technology ABSTRAKPenelitian ini dilatarbelakangi adanya peserta didik yang kurang memiliki rasa empati, serta belum adanya program pelayanan  yang dikembangkan secara khusus untuk meningkatkan  rasa empati peserta didik. Sehingga peneliti tertarik untuk membuat rancangan program layanan yang dapat memudahkan Guru BK untuk mengembangkan empati peserta didik. Penelitian ini bertujuan untuk mengetahui: 1) Profil tingkat empati peserta didik; 2) merancang program pengembangan untuk  meningkatkan kecerdasan emosi remaja dalam aspek empati berbasis Teknologi Informasi yang dapat diterima secara teoritis dan praktis. Metode penelitian ini adalah kuantitatif jenis deskriptif dan pengembangan. Teknik pengumpulan data yang digunakan adalah angket. Subjek dalam penelitian ini adalah peserta didik kelas XII IPA 3 SMAN 2 Bungo yang berjumlah 33 orang. Pakar teoritis terdiri dari 3 orang dosen, pakar praktis Guru Bimbingan dan Konseling dan pakar media adalah guru Teknologi informasi. Prosedur pengembangan yang digunakan dalam penelitian ini meliputi 5 langkah yaitu: 1) Potensi dan masalah; 2) pengumpulan data; 3) desain produk, 4) validasi desain, 5) revisi desain. Teknik analisis data  yang digunakan adalah presentase. Hasil dari perhitungan skor masing-masing validasi yang dilakukan dicari rata-rata skor perolehannya kemudian dapat dikonversikan dari data kuantitatif ke data kualitatif. Hasil penelitian ini mengungkapkan  bahwa: 1) profil tingkat empati peserta didik di berada pada kategori sedang; 2) aplikasi yang telah divalidasi oleh pakar teoritis, praktis, dan media dikategorikan  sangat diterima. Artinya, program yang dikembangkan layak untuk digunakan untuk meningkatkan empati peserta didik di sekolah. Kata Kunci : Pengembangan prgra, empati, teknologi informasi.